Focus Assessment of Transthoracic Echocardiography post septostomy Procedure in Patients Undergoing Ablation of Left Atrial Supraventricular Tachycardia - Al- Alwany, Ameen A.; Mansour, Marwa A. (Journal of the Faculty of Medicine Baghdad, 2022)
Background: Echocardiography has an important role to follow up patients with Iatrogenic atrial septal defect (IASD) and after Catheter ablation during electro-physiological study.Objectives: evaluating the impact of non-invasive Transthoracic Echocardiography (TTE) parameters (LAVI, LVEF, ASD size and E/e`) post radiofrequency ablation of left atrial arrhythmia.Patients and methods: for the evaluation of the atrial septal defect, a transthoracic echocardiography (TTE) was used   in patients who underwent left atrial arrhythmia ablation, enrolled in prospective study in the Iraqi center for cardiac diseases, in cooperation with university of Baghdad /college of medicine  Results: The outcomes of the present study were assessed according to Transthoracic Echocardiographic parameters with a median period of follow up of six months post-radiofrequency procedure for each patient. The mean of age was (36.28±10.34 years), females were 24 (51.1%) while males were 23 (48.9%), with no structured heart diseases and normal LV function with mean EF (64.68± ,5.23%) and the mean LA diameter (35.75±,2.92mm). Iatrogenic atrial septal defects (IASDs) were detected by TTE in all patients with range from (2-5) mm with mean of (3.47±0.92). Also we noticed that patients with smaller ASD size had higher LVEF than those who had larger ASD size with (P=0.007), while there was no significant association between ASD size with left atrial volume index (LAVI) and E/e`.  Conclusions: Non-invasive Transthoracic Echocardiography (TTE) study that was used post atrial septostomy for monitoring the closure of residual atrial septal defect is useful and applicable. And may be used in daily practise post atrial septostomy procedure and recommended rather than the use of invasive Transoesophageal Echocardiography (TEE).